Preparation method of high-purity alumina electrostatic chuck ceramic

By improving the formulation process of high-purity alumina ceramics and improving the dispersion effect of the slurry, the problem of insufficient powder dispersion during the ceramic preparation process is solved, and the high density, uniformity and performance of the ceramics are improved, meeting the needs of high-precision applications.

CN119797893APending Publication Date: 2025-04-11JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD

Patent Information

Application Number
CN202411638395.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

At this stage, high-purity alumina ceramics have problems with insufficient powder dispersion during the preparation process, resulting in poor quality of green bodies, affecting the density, uniformity and performance of the final ceramics.

Method used

By improving the formulation process, changing the type and proportion of the adhesive, and adjusting the order of the adhesive added, the dispersion effect of the slurry is improved, thereby preparing a cast green body with better quality. Specific steps include ball milling, casting, preparation of electrodes, drilling, lamination, glue discharge, sintering, leveling and thermal isostatic pressure treatment.

Benefits of technology

It significantly improves the density and uniformity of high-purity alumina ceramics, reduces internal defects, enhances its mechanical and electrical properties, and meets the strict requirements in high-precision application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of high-purity alumina electrostatic chuck ceramic, which belongs to the technical field of electrostatic chucks, and comprises the following steps: a) ball milling: mixing high-purity alumina powder with an organic binder, a dispersant and a solvent, and carrying out ball milling treatment; b) tape casting: spreading the aluminum oxide slurry on a tape casting machine through a tape casting process to form a ceramic film, and forming an aluminum oxide ceramic green body; c) preparing an electrode: preparing an electrode layer arranged in the ceramic; d) punching: reserving electrode through holes and holes required by other designs on the formed aluminum oxide ceramic body; e) laminating: laminating a plurality of layers of ceramic films to form a ceramic green body; f) glue discharging: placing the laminated ceramic green body in a glue discharging furnace for heating treatment; g) sintering: performing high-temperature sintering on the degummed ceramic green body; h) leveling: carrying out leveling treatment on the sintered ceramic to enable the surface of the ceramic to be flat; and i) hot isostatic pressing treatment: placing the leveled ceramic main body in hot isostatic pressing equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for preparing high-purity alumina electrostatic chuck ceramics. Background Art

[0002] High-purity alumina ceramics are a material widely used in electrostatic chucks. Due to its high hardness, excellent insulation properties, high temperature resistance, and corrosion resistance, it has become an indispensable material in high-precision industries such as semiconductors, displays, and optical devices. Tape casting is one of the important processes for preparing high-purity alumina ceramics. The tape casting method can produce green bodies with high density and uniform structure. However, there are still some technical difficulties in the preparation process of high-purity alumina ceramics at this stage, especially due to the dispersion problem of powders, resulting in poor green body quality, which affects the performance of the final ceramics.

[0003] Patent CN102134872B proposes that if the alumina ceramic powder is not dispersed sufficiently during the ball milling dispersion process, agglomeration is likely to occur, resulting in poor uniformity of the tape-cast green body and defects such as pores and cracks. These defects will not only reduce the mechanical strength of the ceramic, but also affect its insulation performance and surface finish, making the performance of the final product unstable. Therefore, how to improve the dispersibility of alumina powder and prepare dense and uniform tape-cast green bodies is an important way to improve the performance of high-purity alumina ceramics.

[0004] To solve this problem, the present invention proposes a technical solution to improve the performance of high-purity alumina ceramics by improving the formulation process. By changing the type and proportion of bonding and the order of adding the binder, the dispersion effect of the slurry is effectively improved, thereby preparing a tape-cast green body with better quality. This optimized process can significantly improve the density and uniformity of high-purity alumina ceramics, reduce internal defects, and further enhance its mechanical and electrical properties to meet the strict requirements in high-precision application scenarios. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing high-purity alumina electrostatic chuck ceramics, improve the density and uniformity of high-purity alumina ceramics, reduce internal defects, and further enhance their mechanical properties and electrical properties.

[0006] In order to solve the above technical problems, the technical solution of the present invention is:

[0007] A method for preparing high-purity alumina electrostatic chuck ceramics, the method comprising:

[0008] a) Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant and a solvent, and subjected to ball milling to prepare an alumina slurry with a uniform particle size distribution;

[0009] b) tape casting: the alumina slurry is spread into a ceramic film on a tape casting machine through a tape casting process to form an alumina ceramic body;

[0010] c) preparing electrodes: preparing an electrode layer disposed inside the ceramic so that the ceramic disk generates adsorption force;

[0011] d) Punching: Preserve electrode through holes and other holes required by the design on the formed alumina ceramic body;

[0012] e) Lamination: aligning and laminating the multi-layer ceramic film with the electrode layer to form a multi-layer structured ceramic body;

[0013] f) Debinding: placing the laminated ceramic body in a debinding furnace for heating to remove organic binders and adhesives;

[0014] g) Sintering: Sintering the ceramic body after debinding at high temperature to form a densified ceramic body;

[0015] h) Leveling: Leveling the sintered ceramics to make the surface of the ceramics flat;

[0016] i) Hot isostatic pressing: The flattened ceramic body is placed in a hot isostatic pressing device and processed under high temperature and high pressure to further improve the density and mechanical properties of the ceramic.

[0017] Preferably, in the step a), the solvent is any one of toluene, ethanol, ethyl acetate, isopropanol or a mixture of any two or more thereof, the volume of the solvent accounts for 40% to 60% of the total amount of the slurry, the binder is polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl pyrrolidone (PVP) or an acrylate polymer, the mass of the binder accounts for 2% to 10% of the total amount of the ceramic powder, the dispersant is ammonium polyacrylate, sodium polyacrylate or triethanolamine, and the amount of the dispersant added is 0.2% to 1% of the total amount of the ceramic powder.

[0018] Preferably, in the step a), the high-purity alumina powder and the dispersant are first ball-milled and then the solvent is added. The first ball-milling time is 12 to 24 hours, and the percentage of the solvent in the total solvent is 30% to 80%. The binder is premixed before being added to the ball mill, and the premixed solvent accounts for 20% to 70%. After the premixing, it is added for a second ball-milling, and the second ball-milling time is 12 to 36 hours.

[0019] Preferably, the adhesive in step a) is any one of a low molecular weight adhesive, a medium molecular weight adhesive, and a high molecular weight adhesive, or a mixture of two thereof, wherein the molecular weight of the low molecular weight adhesive is 1000 to 10000 Da, the molecular weight of the medium molecular weight adhesive is 10000 to 100000 Da, and the molecular weight of the high molecular weight adhesive is greater than 100000 Da.

[0020] Preferably, in the step b), the thickness of the alumina ceramic body is 50 to 500 microns, and the required thickness is controlled by adjusting the gap between the casting blades and the viscosity of the slurry.

[0021] Preferably, in step c), the electrode is prepared by any one of screen printing, sputtering deposition, evaporation and lamination, and the conductive material in the electrode is any one of molybdenum, tungsten, silver and conductive oxide.

[0022] Preferably, the lamination in step e) is performed by mechanical lamination using any one of mechanical pressing lamination, hot pressing lamination, WIP, and vacuum lamination, and an alignment fixture is used to ensure accurate alignment of each layer of ceramic film with the electrode layer. The laminated structure forms a stable ceramic body under heating and pressing.

[0023] Preferably, in the step f), the debinding temperature is 300-600° C. and the debinding time is 50-100 hours, so as to completely remove the organic matter while maintaining the integrity of the ceramic body.

[0024] Preferably, in step g), high temperature sintering needs to be carried out in a vacuum, inert gas environment or reducing gas environment, with a sintering temperature of 1400-1800° C. and a holding time of 2-6 hours to prevent oxidation and sinter into porcelain, thereby ensuring high purity and high performance of the ceramic.

[0025] Preferably, in the step h), the leveling is achieved by mechanical grinding, polishing and pressing, and the flatness is controlled to be 50-500 um, thereby reducing the pre-flatness and enabling the subsequent steps to better improve the flatness.

[0026] The above technical solution has the following beneficial effects:

[0027] 1. Improve the density of ceramics

[0028] Good dispersibility ensures that the powder particles are evenly distributed in the slurry, reducing agglomeration, so that the gaps can be filled more effectively during the casting and sintering process, thereby improving the density of the ceramic and ultimately making the ceramic material stronger;

[0029] 2. Reduce defects

[0030] Powders with good dispersion can effectively reduce the generation of defects such as pores and cracks. This is because evenly dispersed particles can better approach each other during the molding and sintering process, avoiding stress concentration and defect generation caused by large particles or agglomerates.

[0031] 3. Improve mechanical properties

[0032] The mechanical properties of ceramics, such as hardness and strength, are directly related to the microstructure of the material. A good dispersion effect can improve the microstructure of ceramics, increase the hardness and impact resistance after sintering, and thus extend the service life of ceramic products. DETAILED DESCRIPTION

[0033] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] Example 1

[0035] A method for preparing high-purity alumina electrostatic chuck ceramics, comprising:

[0036] a) Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant and a solvent, and subjected to ball milling to prepare an alumina slurry with a uniform particle size distribution;

[0037] The solvent is any one of toluene, ethanol, ethyl acetate, isopropanol or a mixture of any two or more thereof, the volume of the solvent accounts for 40% to 60% of the total amount of the slurry, the binder is polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl pyrrolidone (PVP) or an acrylic polymer, the mass of the binder accounts for 2% to 10% of the total amount of the ceramic powder, the dispersant is polyacrylic acid ammonium salt, polyacrylic acid sodium salt or triethanolamine, and the amount of the dispersant added is 0.2% to 1% of the total amount of the ceramic powder;

[0038] In some embodiments, the solvent is toluene or ethanol or ethyl acetate or isopropanol, or a mixture of any two of toluene, ethanol, ethyl acetate, and isopropanol, or a mixture of any three of toluene, ethanol, ethyl acetate, and isopropanol, or a mixture of toluene, ethanol, ethyl acetate, and isopropanol, and the volume of the solvent accounts for 40% or 60% of the total amount of the slurry, or the volume of the solvent accounts for 50% of the total amount of the slurry;

[0039] In some embodiments, the binder is any one of polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl pyrrolidone (PVP), and acrylic polymers, and the mass of the binder accounts for 2% or 10% of the total amount of the ceramic powder, or it can also account for 5% or 8% of the total amount of the ceramic powder; the dispersant is any one of polyacrylic acid ammonium salt, polyacrylic acid sodium salt, and triethanolamine, and the amount of the dispersant added is 0.2% or 1% of the total amount of the ceramic powder, or the amount of the dispersant added is 0.6% of the total amount of the ceramic powder;

[0040] Among them, in the above a), the high-purity alumina powder and the dispersant are first ball-milled, and then the solvent is added. The time of the first ball milling is 12 to 24 hours, and the percentage of the solvent in the total solvent is 30% to 80%. The binder is premixed before being added to the ball mill, and the premixed solvent accounts for 20% to 70%. After the premixing, it is added for the second ball milling, and the time of the second ball milling is 12 to 36 hours;

[0041] In some embodiments, the first ball milling time is 12 hours or 24 hours, the amount of solvent added after the first ball milling accounts for 30% or 80% of the total solvent, and correspondingly, the percentage of the solvent in the premixing is 70% or 20% of the total solvent, and the second ball milling is performed after the premixing, and the second ball milling time is 12 hours or 36 hours, or 24 hours, to prepare an alumina slurry with a uniform particle size distribution;

[0042] Wherein, in the above a), the adhesive is any one selected from a low molecular weight adhesive, a medium molecular weight adhesive, and a high molecular weight adhesive, or a mixture of any two of a low molecular weight adhesive, a medium molecular weight adhesive, and a high molecular weight adhesive, or a mixture of a low molecular weight adhesive, a medium molecular weight adhesive, and a high molecular weight adhesive, the molecular weight of the above low molecular weight adhesive is 1000 to 10000Da, such as the molecular weight of the low molecular weight adhesive is 5500Da, the molecular weight of the medium molecular weight adhesive is 10000 to 100000Da, such as the molecular weight of the medium molecular weight adhesive is 55000Da, and the molecular weight of the high molecular weight adhesive is greater than 100000Da, such as the molecular weight of the high molecular weight adhesive is 110000Da;

[0043] b) tape casting: the alumina slurry is spread into a ceramic film on a tape casting machine through a tape casting process to form an alumina ceramic body;

[0044] The thickness of the alumina ceramic body is 50 to 500 microns, and the required thickness is controlled by adjusting the gap between the casting blades and the viscosity of the slurry. In some embodiments, the thickness of the alumina ceramic body is 50 microns or 500 microns, and the thickness can also be 250 microns or 300 microns, which can be set as needed.

[0045] c) preparing electrodes: preparing an electrode layer disposed inside the ceramic so that the ceramic disk generates adsorption force;

[0046] Wherein, the electrode is prepared by any one of screen printing, sputtering deposition, evaporation, and pressing, and the conductive material in the electrode is any one of molybdenum, tungsten, silver, and conductive oxide. In some embodiments, the electrode is prepared by screen printing, sputtering deposition, evaporation, pressing, etc., and the conductive material in the electrode is molybdenum or tungsten or silver or conductive oxide;

[0047] d) Punching: electrode through holes and other holes required by the design are reserved on the formed alumina ceramic body. The electrode through holes are used to set electrodes for easy power supply;

[0048] e) Lamination: aligning and laminating a plurality of ceramic films with an electrode layer to form a ceramic body with a multi-layer structure; wherein the lamination is performed by mechanical lamination, hot pressing lamination, wip, or vacuum lamination, and an alignment fixture is used to ensure that each layer of the ceramic film is accurately aligned with the electrode layer, and the laminated structure forms a stable ceramic body under heating and pressing;

[0049] f) Debinding: placing the laminated ceramic body in a debinding furnace for heating to remove organic binders and adhesives;

[0050] The debinding temperature is 300-600°C, and the debinding time is 50-100 hours, so as to completely remove organic matter while maintaining the integrity of the ceramic body. In some embodiments, the debinding temperature is 300°C or 600°C, the debinding temperature can also be 450°C, the debinding time is 50 hours or 100 hours, and the debinding time can also be 75 hours;

[0051] g) Sintering: The ceramic body after debinding is subjected to high-temperature sintering to form a densified ceramic body; wherein, the high-temperature sintering needs to be carried out in a vacuum, an inert gas environment or a reducing gas environment, the sintering temperature is 1400-1800°C, and the holding time is 2-6 hours to prevent oxidation and sinter into porcelain, ensuring the high purity and high performance of the ceramic. In some embodiments, the high-temperature sintering needs to be carried out in a vacuum or an inert gas environment, the sintering temperature is 1400°C or 1800°C, the sintering temperature can be 1600 degrees Celsius, the high-temperature holding time is 2 hours or 6 hours, and the holding time can also be 4 hours;

[0052] h) Leveling: The sintered ceramic is leveled to make the ceramic surface flat, wherein the leveling is achieved by mechanical grinding, polishing and pressing, and the flatness is controlled to be 50-500um, and the pre-flatness is reduced so that the subsequent steps can better improve the flatness. In some embodiments, the flatness after leveling is 50um or 500um, or 250um or 300um;

[0053] i) Hot isostatic pressing (HIP): The flattened ceramic body is placed in a hot isostatic pressing device and processed under high temperature and high pressure to further improve the density and mechanical properties of the ceramic;

[0054] The preparation method of the electrostatic chuck ceramic disc of the present application enhances the density and hardness of the ceramic by improving the dispersibility and reduces defects, which can not only extend the service life of the electrostatic chuck ceramic, but also is particularly helpful for its long-term application in a plasma environment; the dense and defect-free alumina ceramic has higher corrosion resistance and erosion resistance, can effectively resist particle bombardment and chemical corrosion in a plasma environment, and reduce surface damage and material degradation; the optimized ceramic material can be used for a longer time in a plasma environment, ensuring that the electrostatic chuck can continue to operate stably under harsh working conditions;

[0055] In the preparation method of the electrostatic chuck ceramic disc of the present application:

[0056] 1. Optimization of binder types and proportions:

[0057] Use low molecular weight, medium molecular weight and high molecular weight binders for mixing, use one or two binders at the same time, use binders in different proportions, test the dispersion effect of binders in different proportions, test the particle size after dispersion, record different particle size data, make products, and finally test the density, hardness and other properties of the products;

[0058] 2. Optimization of binder addition order:

[0059] Comparative example: a binder, powder and other organic matter are added to a ball mill for ball milling; Example: the powder and dispersant are first mixed, and then a binder is added for ball milling again. The two methods are compared to compare the effect of the order of adding the binder on the dispersibility;

[0060] The details are shown in Table 1 below:

[0061] Table 1

[0062]

[0063] Wherein, binder A is a low molecular weight binder, binder B is a medium molecular weight binder, and binder C is a high molecular weight binder;

[0064] Conclusion: In studying the effect of binders on the dispersion of ceramic powders, the experimental results show that the type and ratio of binders have a significant effect on dispersibility. In particular, when low molecular weight and medium molecular weight binders are mixed in a ratio of 3:7, the dispersion effect is best; this ratio can balance the fluidity of the slurry and the binding force between particles, significantly reducing the agglomeration of powders and improving the uniformity and stability of the slurry;

[0065] In addition, when used alone, medium molecular weight binders show the best effect on dispersibility. Medium molecular weight binders can provide appropriate viscosity and adsorption to ensure good dispersion of ceramic powder in the slurry, prevent particle agglomeration and sedimentation, and maintain good fluidity of the slurry.

[0066] Among the components with better dispersion effects, the density and hardness of the final prepared ceramic products are also significantly improved. This shows that optimizing the type and proportion of binders can not only improve the dispersibility of ceramic powders, but also enhance the physical properties of ceramic materials, such as density and hardness, thereby improving the overall quality and service life of alumina electrostatic chuck ceramics;

[0067] The principle of binder affecting powder dispersion can be explained from the following aspects:

[0068] 1. Physical connection between particles

[0069] Function of binder: Binder is a viscous material that can form a physical connection between ceramic powder particles. In ceramic slurry, binder temporarily binds powder particles together through its adhesion. This physical connection can provide certain strength and shape stability for ceramic green body, and prevent powder particles from falling off or uneven dispersion during molding.

[0070] Influencing mechanism: However, if the physical connection of the binder is not controlled, it may lead to excessive bonding between particles, making it difficult for the particles to be evenly dispersed in the slurry. This excessive bonding will increase the viscosity of the slurry, resulting in the particles being unable to move freely, increasing the possibility of particle agglomeration, and thus reducing the dispersion effect;

[0071] 2. Adsorption on particle surface

[0072] Adsorption of binders: Binders can usually be adsorbed on the surface of powder particles to form a thin film. This film can change the surface properties of the particles, such as surface energy, polarity, etc., thereby affecting the interaction between particles;

[0073] Influencing mechanism: If the binder is properly adsorbed, it can form a uniform covering layer on the particle surface, reduce direct contact between particles, prevent agglomeration, and enhance dispersibility. However, if the binder is adsorbed too much, it will increase the adhesion between the particle surfaces, making the particles more likely to agglomerate and reducing dispersibility.

[0074] 3. Influence on slurry viscosity

[0075] Viscosity increase mechanism: After the binder is dissolved in the slurry, the overall viscosity of the slurry will increase. This is because the binder molecules interact with the solvent molecules in the solution to form a complex molecular chain network structure, thereby increasing the flow resistance of the slurry;

[0076] Influencing mechanism: Higher slurry viscosity will restrict the movement of powder particles, making it difficult to evenly distribute them in the liquid phase, resulting in particle aggregation and sedimentation. Therefore, while the binder increases the slurry viscosity, it may also inhibit the dispersion of the powder. The proportion and viscosity control of the binder are crucial to maintaining good fluidity of the slurry;

[0077] 4. Interface chemical effects

[0078] Chemical adsorption and electrostatic interaction: Some binders can interact with the surface of ceramic particles through chemical adsorption or electrostatic interaction; this chemical adsorption or electrostatic interaction helps to stabilize the dispersion of particles in the slurry and reduce the agglomeration of particles;

[0079] Influence mechanism: If the binder can stably adsorb to the particle surface, it can prevent the particles from agglomerating in the solution by shielding the electrostatic attraction or van der Waals force between the particles. This interfacial chemical effect helps to improve the dispersion performance of the powder;

[0080] 5. Impact on performance during drying and sintering

[0081] Volatilization or decomposition of binders: During the drying or sintering process, binders usually evaporate or decompose, which will affect the structure and density of the ceramic green body; if the binder is unevenly distributed or incompletely retained, pores or defects may be formed inside the ceramic, which will affect the density and strength of the final product;

[0082] Mechanism of influence: During the drying or sintering process, when the binder evaporates, if the distribution is uneven, it may cause uneven shrinkage or residual material in local areas, resulting in defects in the microstructure; these defects will affect the final properties of the ceramic, especially density, hardness and strength.

[0083] 6. Interaction between binder and dispersant

[0084] Synergistic and competitive effects: The interaction between the binder and the dispersant in the slurry will also affect the dispersibility of the powder; the main function of the dispersant is to make the particles more evenly dispersed in the solution by changing the surface properties or electrostatic potential of the particles; while the function of the binder is to bind the particles together and increase the strength of the green body;

[0085] Influence mechanism: If the binder and dispersant work well together, the dispersant can help the particles disperse better, while the binder can increase the strength of the green body without destroying the dispersibility. However, if the binder and dispersant compete with each other (for example, the binder covers the adsorption sites of the dispersant), the dispersant effect may be weakened, affecting the dispersibility of the powder.

[0086] The influence of binders on powder dispersion is multi-layered, with both positive and negative effects. Binders affect the dispersion of powders in slurries through multiple mechanisms such as physical connection, adsorption, viscosity adjustment, and interfacial chemical effects. To optimize the dispersibility of ceramic powders, it is necessary to precisely control the amount, type, and use of binders, while paying attention to their interactions with dispersants and other ingredients.

[0087] Compared with the prior art, this application has the following advantages:

[0088] 1. Improve the density of ceramics

[0089] Good dispersibility ensures that the powder particles are evenly distributed in the slurry, reducing agglomeration, so that the gaps can be filled more effectively during the casting and sintering process, thereby improving the density of the ceramic and ultimately making the ceramic material stronger;

[0090] 2. Reduce defects

[0091] Powders with good dispersion can effectively reduce the generation of defects such as pores and cracks. This is because evenly dispersed particles can better approach each other during the molding and sintering process, avoiding stress concentration and defect generation caused by large particles or agglomerates.

[0092] 3. Improve mechanical properties

[0093] The mechanical properties of ceramics, such as hardness and strength, are directly related to the microstructure of the material. A good dispersion effect can improve the microstructure of ceramics, increase the hardness and impact resistance after sintering, and thus extend the service life of ceramic products.

[0094] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing high-purity alumina electrostatic chuck ceramics, characterized in that: The preparation method comprises: a) Ball milling: High-purity alumina powder is mixed with an organic binder, a dispersant and a solvent, and subjected to ball milling to prepare an alumina slurry with a uniform particle size distribution; b) tape casting: the alumina slurry is spread into a ceramic film on a tape casting machine through a tape casting process to form an alumina ceramic body; c) preparing electrodes: preparing an electrode layer disposed inside the ceramic so that the ceramic disk generates an adsorption force; d) Punching: Preserve electrode through holes and other holes required by the design on the formed alumina ceramic body; e) Lamination: aligning and laminating the multi-layer ceramic film with the electrode layer to form a multi-layer structured ceramic body; f) Debinding: The laminated ceramic body is placed in a debinding furnace for heating to remove organic binders and adhesives; g) Sintering: Sintering the ceramic body after debinding at high temperature to form a densified ceramic body; h) Leveling: Leveling the sintered ceramics to make the surface of the ceramics flat; i) Hot isostatic pressing (HIP): The flattened ceramic body is placed in a hot isostatic pressing device and processed under high temperature and high pressure to further improve the density and mechanical properties of the ceramic.

2. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In the step a), the solvent is any one of toluene, ethanol, ethyl acetate, and isopropanol, or a mixture of any two or more thereof, the volume of the solvent accounts for 40% to 60% of the total amount of the slurry, the binder is polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl pyrrolidone (PVP) or an acrylate polymer, the mass of the binder accounts for 2% to 10% of the total amount of the ceramic powder, the dispersant is ammonium polyacrylate, sodium polyacrylate or triethanolamine, and the amount of the dispersant added is 0.2% to 1% of the total amount of the ceramic powder.

3. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In the step a), the high-purity alumina powder and the dispersant are first ball-milled and then the solvent is added. The first ball-milling time is 12 to 24 hours, and the percentage of the solvent in the total solvent is 30% to 80%. The binder is premixed before being added to the ball mill, and the premixed solvent accounts for 20% to 70%. After the premixing, it is added for the second ball-milling, and the time for the second ball-milling is 12 to 36 hours.

4. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: The adhesive in step a) is any one of a low molecular weight adhesive, a medium molecular weight adhesive, and a high molecular weight adhesive, or a mixture of two of them, wherein the molecular weight of the low molecular weight adhesive is 1000-10000Da, the molecular weight of the medium molecular weight adhesive is 10000-100000Da, and the molecular weight of the high molecular weight adhesive is greater than 100000Da.

5. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In the step b), the thickness of the alumina ceramic body is 50 to 500 microns, and the required thickness is controlled by adjusting the gap between the casting blades and the viscosity of the slurry.

6. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In the step c), the electrode is prepared by any one of screen printing, sputtering deposition, evaporation and pressing, and the conductive material in the electrode is any one of molybdenum, tungsten, silver and conductive oxide.

7. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: The lamination in step e) is performed by mechanical lamination using any of mechanical pressing lamination, hot pressing lamination, WIP, and vacuum lamination, and an alignment fixture is used to ensure accurate alignment of each layer of ceramic film with the electrode layer. The laminated structure forms a stable ceramic body under heating and pressing.

8. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In the step f), the debinding temperature is 300-600° C. and the debinding time is 50-100 hours, so as to completely remove organic matter while maintaining the integrity of the ceramic body.

9. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In step g), high temperature sintering needs to be carried out in a vacuum, inert gas environment or reducing gas environment, with a sintering temperature of 1400-1800° C. and a holding time of 2-6 hours to prevent oxidation and sinter into porcelain, thereby ensuring high purity and high performance of the ceramic.

10. The method for preparing a high-purity alumina electrostatic chuck ceramic according to claim 1, characterized in that: In the step h), the leveling is achieved by mechanical grinding, polishing and pressing, and the flatness is controlled to be 50-500 um, thereby reducing the pre-flatness and enabling the subsequent steps to better improve the flatness.

Citation Information

Patent Citations

  • Drain cover of wash basin

    CN102134872A

Cited By

  • Alumina-based composite ceramic material and preparation method thereof

    CN120622907A